Rancang Bangun Sistem Informasi Akademik Berbasis Website di Madrasah Sirajun Jadid Kecamatan Pontianak Barat - Mawaddah, Mawaddah; Maulana, Adha; Hidayati, Awanis (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Madrasah Sirajun Jadid is a potential school in Pontianak city that has adequate facilities and infrastructure. However, this school still uses a manual system that is less effective in managing academic data and information. Therefore, a web-based academic information system is needed that can make it easier for teachers to manage data and information, and make it easier for students to obtain academic information. The design method used is (RAD) Rapid Application Development which is one of the system development strategy methods through the involvement of extensive use in the use of a series of constructions. The results of this study are that the Madrasah Sirajun Jadid website application can run well. The features displayed can help users in inputting data. Based on the results of testing users on the application as a whole, it has received a good response with a percentage reaching 87%, so it can be concluded that this application can be used as a Madrasah Sirajun Jadid website application.